Performance analysis of consolidated sorbent based closed thermochemical energy storage reactor for environmental sustainability. (20th August 2020) - Li, Wei; Klemeš, Jiří Jaromír; Wang, Qiuwang; Zeng, Min
Abstract: Adsorption thermochemical energy storage (TCES) is currently a momentous technique utilised for long-term energy storage due to the reversible gas-solid reaction under low-temperature. A novel 3D heat storage reactor, including two shaped columnar sorbent reactive beds is proposed. The heat charging (dehydration) and discharging (hydration) processes under different operating conditions are numerically investigated. The roughly uniform temperature and conversion degree evolutions of the bed during reaction suggest a good heat and mass transferability of the porous shaped sorbent bed. For reference cases, the time required to finish the dehydration and hydration processes are 328 and 748 min; the decreased condensation temperature and increased evaporation temperature promote dehydration and hydration kinetics. The charging power and thermal efficiency increase firstly and decline later till the end of dehydration, the final values are 212 W and 91.1%; while discharging power and efficiency decrease with the advancement of conversion degree, with thermal power and thermal efficiency of 93 W and 87.5%. Moreover, the overall thermal coefficient of performance of 80.9% and exergy coefficient of performance of 27.7% are achieved; and the coefficients of performance can be further optimised at specific charging temperature and flow rate of heat transfer fluid (HTF). All these satisfying performances of this model preliminarily confirm its feasibility in TCES. Highlights: A 3D closed thermochemical energy storage model is proposed. Pressure effect in dehydration and hydration kinetics is investigated. The average charging power is 212 W for this reactor model. Overall COPth and COPex are 80.9% and 27.7%. Specific charging temperature and flow rate of the heating medium further enhanced COP.